Operational resilience disclosures by banks: analysis of annual reports - Martin Leo (Risks, 2020)
An array of developments impacting the financial services industry, such as increasing complexity, interconnectedness, third party dependencies and digitalization, means operational resilience will remain a significant area of concern for policy makers, investors and customers. The purpose of this study is to evaluate if banks are disclosing information on their operational resilience risk. The study initially reviews the regulatory landscape for operational resiliency. The recent annual reports of the GSIB banks are reviewed to identify if they have made references to operational resilience. Through text mining, a frequency analysis of terms related to operational resilience was done, followed by an evaluation to understand the existence of relationships between these terms. The study shows that the regulatory guidance for operational resilience is still evolving with much of the current impetus on cybersecurity. There is a notable gap between banks that have reported on operational resiliency and those that have not, with a few patterns visible. Research in the area of operational resilience is relatively new and limited, and this research for the first time analyses the disclosures related to operational resilience in annual reports. Further, for policymakers, it highlights the disparity in disclosures around this relatively new area of risk, thus calling for additional regulatory guidance.
Keywords: 330; operational resilience; operational risk; bank; GSIB